OPTIMALISASI TATA KELOLA KINERJA PERANGKAT DESA WERANGGERE KABUPATEN FLORES TIMUR - Stanislaus Vebrianto Bala Leba; Marianus Kleden; Indriyati (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This community service activity was carried out in Weranggere village, Witihama sub-district, East Flores regonicy. This activity took the form of socialization using lecture, discussion, and question and answer methods. The use of the lecture method was 50%, discussion 25% and question and answer 25%. The efforts made in this activity were to provide knowledge and understanding of optimizing the performance governance of village officials. The material presented was attended by village officials and the entire community. Based on the results of the socialization carried out in the service activity, it was found that the data processing process was still manual and not integrated with technology, such as the use of paper and books to record data. Another problem is the lack of human resources and inadequate technology. This can affect the efficiency and effectiveness of work, as well as the quality of services provided. Based on the results of the service activities in Weranggere Village, it is concluded that there is a need for activities in the form of socialization to improve the performance of village officials, which is not optimal. as for the improvement of governance that can be observed from the service activities for two months, namely in the form of changes in the accuracy of working hours, apparatus participation, cooperation of village officials and apparatus. Weranggere Village is one of the villages that is very high in tolerance, so in this case the village government must maintain the values of justice so that the service process to the community is not tense.